Relationship between spouse abuse, social support and perceived stress in women with ‎addicted and non-addicted husbands in Rasht city - Seyed Omid Sotodeh Navroi; Shina Zeinali; Nooshin Khasteganan (Guilan University of Medical Sciences, 2012)
Introduction: Spouse abuse is a major human health and lawful problem and it refers to any violent ‎sex related behavior that results in women s physical, sexual and mental suffering. In attention that ‎spouse abuse has complications and unsatisfactory social and family outcomes, it is necessary to ‎identify factors which hinder family function. ‎ Objective: The study assessed and compared the relationship between spouse abuse, social support ‎and perceived stress in women with addicted and non-addicted husbands in Rasht city.‎ Method: This is a descriptive analytical study. The sample consisted of ‎‏100‏‎ women (‎‏50‏‎ with ‎addicted husbands and ‎‏50‏‎ with non-addicted husbands) who were selected by convenience ‎sampling and answered the questionnaires of perceived stress, social support, and spouse abuse. The ‎data was analyzed using statistical tests of independent T test, and correlation. ‎ Result: The analyzed data showed that there was a significant difference between variables of ‎spouse abuse and its subscales ( physical, emotional, sexual, behavioral), social support, perceived ‎stress, and its subscales(tangible support, emotional support, giving information, kindness, social ‎interaction and total perceived stress score) in women with addicted and non-addicted husbands ‎‎(p<‎‏0.01‏‎).‎ Conclusion: The results showed that the amount of social support, perceived stress and spouse ‎abuse is different between women with addicted husbands and women with non-addicted ‎husbands. Therefore, training programs are more required for making a supportive environment to ‎reduce vulnerability and damage on families with addicted individuals. ‎